The Effectiveness of Abdominal Stretching Exercise and Classical Music Therapy on Dysmenorrhore Pain Intensity among Adolescent Women - Anggraini, Tasya; Muhaimin, Toha; Nurhayati, Nurhayati; Basri, Achmad Ali (GLOBAL HEALTH SCIENCE GROUP, 2024)
The prevalence of dysmenorrhea was high in all the countries and caused a decrease in quality of life among adolescents. One of the recommendations to reduce pain is abdominal stretching exercises and classical music therapy. However, limited studies were found to know the comparison of both interventions. Objective. This study aimed to explore the effectiveness of abdominal stretching exercises compared to classical music therapy on dysmenorrhoea pain intensity among adolescent women. Methods: This study is quasi-experimental with pre-test and post-test design using a convenience sampling method. During one one-month period from August to September 2023, this study was conducted among adolescents. The inclusion criteria were adolescent women who experienced menstruation pain, were in stable condition, not taking any painkiller medication the exclusion criteria were respondents with chronic conditions. A total of 38 respondents divided into two groups agreed to participate in this study. The instrument used is the NRS (Numerical Rating Scale) from 0-10. The researcher provided the abdominal stretching exercise for 15 minutes while the classical music therapy intervention for 15-20 minutes for 3 days. Data was analyzed using the Independent T-test. Results. The majority of respondents before intervention were in moderate pain and after intervention decreased in mild and moderate pain. Both interventions were significant in reducing pain with a p-value <0.005. Conclusion: Abdominal Stretching more effective in reducing the intensity of dysmenorrhea pain compared to classical music therapy